Hot gas implant welding of polypropylene via a three-dimensional porous copper implant. (June 2021) - Zhao, Pu; Tian, Lin; Cui, Xu; Xiong, Xuhai; Wang, Daosheng; Li, Guiyang
Abstract: There is an increasing need for joining technologies of thermoplastics, in which hot gas welding is one of the most promising methods. In this paper, an innovative hot gas implant welding technology was used for the bonding of polypropylene (PP). The hot gas implant welding of PP plates was conducted under different heating time ( t h ) in this research, while porous copper was selected as heat transfer implant. The evolution of temperature with t h in the welding joint was recorded using thermocouples while the heat distribution was simulated using COMSOL. The test results of the temperature evolution law of the welding interface perfectly matched the simulation results, and directly affected the distribution of welding joint defects. The more t h produced by the higher heat input promoted the resin fusion at the interface, which was propitious to reduce the generation of defects. Moreover, the mechanical strength of the hot gas implant welding joint was investigated by tensile lap shear strength (LSS) test. When t h = 30 s, the welding joint can reach a maximum mechanical strength of 8.55 MPa, which mean the PP can be joined effectively when the porous copper was selected as a heat transfer implant. The failure interface morphology of different t h was characterized by scanning electron microscopy (SEM), and the characteristic area of the failure interface shown a strong correlation with t h . Highlights: An innovative hot gas implant welding technology was proposed for the Fusion bonding of thermoplastics. Three-dimensional porous copper was first proposed for heat transfer implant at the welding interface. The influence of t h on joint morphology, mechanical properties and cross-sectional was analyzed.